Legal Implications Of Positive Fictive Application After The Law Of Job Creation Law Is Declared Conditionally Unconstitutional - Sianipar, Febri; Prasetiyo, Hari (LPPM Universitas Lampung, 2023)
Article 175 of Law Number 11 of 2020 changes some of the government administration clauses that have been regulated in the regulation of governmental administration. These changes are related to positive verdicts of fictitious and requests as stipulated in Article 53 of the Law of Creating of Job which amends the clauses of Article 53 of the Government Administration Law. The time limit for establishing a positive fictitious decision has changed from 10 days to 5 days and there is no mechanism for an adjuration to the court of the state administrative to obtain a decision to accept the adjuration. The form of research used is normative juridical with qualitative analysis methods. The results of the study show that fictitious requests are considered legally granted in Article 53 paragraph (4) of Law of Creating of Job without a decision by a Court causing legal uncertainty and because the Law of Creating of Job is declared conditionally unconstitutional, it still refers to the Law Government Administration Act